A rationally designed flagellin-L2 fusion protein induced serum and mucosal neutralizing antibodies against multiple HPV types. Issue 30 (9th July 2019) - Zhang, Ting; Chen, Xue; Liu, Hongyang; Bao, Qifeng; Wang, Zhirong; Liao, Guoyang; Xu, Xuemei
Abstract: The amino terminus of human papillomavirus (HPV) minor capsid protein L2 harbors several conserved neutralizing epitopes, including aa.17–36 (RG-1 epitope) and aa.65–85 consensus epitope (cL2 epitope), which are considered to be promising for the construction of cost-effective pan-HPV vaccine candidates. However, the immunogenicity of L2 epitope/peptide is rather weak, and the neutralizing spectrum induced by single type of L2 antigen is suboptimal. In this study, we constructed L2 concatemer with HPV18/33/58/59 RG-1 epitopes and 16L2 aa.11–88 peptide, and fused it with flagellin, a strong systemic and mucosal adjuvant, by hypervariable region replacement. A copy of cL2 epitope was also introduced to the C-terminus of the recombinant protein. The resultant Fla-5PcL2 protein can be produced in E. coli expression system with high yield and good stability. We assessed the immunogenicity of Fla-5PcL2 in mouse model via systemic and mucosal route, and found that subcutaneous immunization with Fla-5PcL2 induced robust serum neutralizing antibodies against divergent HPV types, while intranasal immunization with Fla-5PcL2 induced remarkable L2-specific IgA and cross-neutralizing antibodies in mucosal secretions, and medium titers of cross-neutralizing antibodies in sera. Moreover, Fla-5PcL2 induced full protection against vaginal HPV challenges. As mucosal antibodies provide the first-line defense at infection sites, and needle-free immunizations may increase vaccine compliance and require less public health resources, our results demonstrate that Fla-5PcL2 is a promising vaccine candidate which possibly meet the need in low-resource regions.